(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
To further increase the adoption of additive manufacturing in the industry, it is important to leverage the technology’s potential for serial production to drive down the cost of manufacturing. The use of high-powered laser beam has been envisaged as the potential technique to improve the productivity of additive manufacturing processes such as laser powder bed fusion. Since a large beam spot size is normally used at high laser power, the rougher surfaces obtained in the as-built condition can be a limitation for medical applications. As such, post processing of the parts manufactured is required to enhance the surface quality. This study investigates the effect of post processing on the surface roughness and mechanical properties of Ti6Al4V manufactured at high laser power. The samples manufactured using developed process parameters were subjected to hot isostatic press annealing and polished by centrifugal barrel finishing. The surface roughness and mechanical properties obtained are presented and discussed.